2015
DOI: 10.1597/12-211
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of UCLP Patients: Surgical and Orthodontic Burden of Care during Growth and Final Orthognathic Surgery Need

Abstract: Patients needing final jaw surgery had a more severe skeletal discrepancy during early childhood. The ANB angle at 5 years allowed doctors to identify 45% of the need for orthognathic surgery. The final craniofacial pattern does not seem to change significantly with early or prolonged orthodontic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 22 publications
3
27
1
Order By: Relevance
“…Therefore, as published in an article evaluating the orthodontic burden of care, 76 percent of the patients needed palatal expansion. 53 Concerning velopharyngeal insufficiency, although the data are not published, the need for velopharyngeal insufficiency surgery in our center is 4 percent and thus significantly lower than what is suggested by the literature on two-stage palatoplasty. 54 Volume 137, Number 2 • Evaluation of Alveolar Cleft Formation…”
Section: Plastic and Reconstructive Surgery • February 2016contrasting
confidence: 58%
“…Therefore, as published in an article evaluating the orthodontic burden of care, 76 percent of the patients needed palatal expansion. 53 Concerning velopharyngeal insufficiency, although the data are not published, the need for velopharyngeal insufficiency surgery in our center is 4 percent and thus significantly lower than what is suggested by the literature on two-stage palatoplasty. 54 Volume 137, Number 2 • Evaluation of Alveolar Cleft Formation…”
Section: Plastic and Reconstructive Surgery • February 2016contrasting
confidence: 58%
“…This group was extrapolated from a large sample of unilateral cleft lip and palate children who had been retrospectively collected for a previous growth study. 18 In order to select a control sample with a comparable class III growth pattern, only the patients from the sample who had needed a Le Fort I osteotomy at the completion of growth were included.…”
Section: Patient Samplementioning
confidence: 99%
“…The mean number of appointments was 24.3 per patient (Semb et al, 2011). Meazzini et al (2013) conducted a study with 62 UCLP patients and assessed the development of craniofacial morphology, the need of orthognathic surgery at the completion of growth, and the orthodontic burden of care. These authors observed that neither earlier nor longer orthodontic treatment altered long-term maxillary growth; that is, because all patients exhibited similar malocclusion severities before orthodontic treatment, the treatment length did not interfere in orthognathic surgery need.…”
Section: Introductionmentioning
confidence: 99%